Unveiling Local Electronic Structure of Lanthanide‐Doped Cs2NaInCl6 Double Perovskites for Realizing Efficient Near‐Infrared Luminescence. Issue 32 (30th September 2022) - Han, Siyuan; Tu, Datao; Xie, Zhi; Zhang, Yunqin; Li, Jiayao; Pei, Yifan; Xu, Jin; Gong, Zhongliang; Chen, Xueyuan
Abstract: Lanthanide ion (Ln 3+ )‐doped halide double perovskites (DPs) have evoked tremendous interest due to their unique optical properties. However, Ln 3+ ions in these DPs still suffer from weak emissions due to their parity‐forbidden 4f–4f electronic transitions. Herein, the local electronic structure of Ln 3+ ‐doped Cs2 NaInCl6 DPs is unveiled. Benefiting from the localized electrons of [YbCl6 ] 3− octahedron in Cs2 NaInCl6 DPs, an efficient strategy of Cl − ‐Yb 3+ charge transfer sensitization is proposed to obtain intense near‐infrared (NIR) luminescence of Ln 3+ . NIR photoluminescence (PL) quantum yield (QY) up to 39.4% of Yb 3+ in Cs2 NaInCl6 is achieved, which is more than three orders of magnitude higher than that (0.1%) in the well‐established Cs2 AgInCl6 via conventional self‐trapped excitons sensitization. Density functional theory calculation and Bader charge analysis indicate that the [YbCl6 ] 3− octahedron is strongly localized in Cs2 NaInCl6 :Yb 3+, which facilitates the Cl − ‐Yb 3+ charge transfer process. The Cl − ‐Yb 3+ charge transfer sensitization mechanism in Cs2 NaInCl6 :Yb 3+ is further verified by temperature‐dependent steady‐state and transient PL spectra. Furthermore, efficient NIR emission of Er 3+ with the NIR PLQY of 7.9% via the Cl − ‐Yb 3+ charge transfer sensitization is realized. These findings provide fundamental insights into the optical manipulation of Ln 3+ ‐doped halide DPs, thus laying a foundation for the future design of efficient NIR‐emitting DPs. Abstract : The authors achieve efficient near‐infrared (NIR) luminescence in lanthanide‐doped Cs2 NaInCl6, with a photoluminescence quantum yield of Yb 3+ up to 39.4% via Cl − ‐Yb 3+ charge transfer sensitization. Temperature‐dependent spectroscopic and theory calculations reveal the characteristic local electron structure of t [YbCl6 ] 3− octahedron in Yb 3+ ‐doped Cs2 NaInCl6, which boosts the NIR emissions of Yb 3+ and Er 3+ through Cl − ‐Yb 3+ charge transfer sensitization.